A New Dip Coating Method Using Supporting Liquid for Forming Uniformly Thick Layers on Serpentine 3D Substrates. Issue 24 (12th November 2019) - Lim, Jongkyeong; Kim, A‐Reum; Kim, Seonghyeon; Lee, Sangmin; Yoo, Dongwoo; Park, Jaechan; Kim, Joonwon
Abstract: Dip coating has demonstrated great potential as a multimaterial coating method providing additional functions to substrates or producing a freestanding microscopic layer upon removal of the substrate. In dip coating, a liquid layer is applied on a substrate by dipping and withdrawing it from a liquid bath, and then curing the layer in air. Thus, manufacturing uniformly thick layers on serpentine 3D substrates is difficult due to the influence of gravity during the prolonged curing process, thus hindering the overall potential applications of this method. Herein, a new dip coating method is proposed to overcome the problems of the conventional method by using an immiscible, density‐matched, and interfacial‐tension‐minimized liquid phase, termed the supporting liquid. This new method is performed by dipping and oscillating a serpentine 3D substrate in a biphasic liquid bath with a small amount of prepolymer solution floating atop the supporting liquid. The prepolymer coating, immersed in the supporting liquid, is then cured. The effect of gravity on the prepolymer coating is eliminated by the buoyancy of the supporting liquid and Laplace pressure is weakened by the minimized interfacial tension. This study demonstrates that the new method can fabricate uniformly thick layers covering the entire surface of a serpentine 3D substrate and can be used during the generation of vascular replicas. Abstract : A new dip coating method to create a uniformly thick final layer on a serpentine 3D substrate is proposed. The prepolymer coating is cured while being immersed in an immiscible, density‐matched, and interfacial‐tension‐minimized liquid phase, termed the supporting liquid. The effect of gravity on the prepolymer coating is eliminated by the buoyancy of the supporting liquid and Laplace pressure is weakened by the minimized interfacial tension.